KONSISTENSI REAKSI PASAR MODAL INDONESIA TERHADAP PENERBITAN INDEKS SRI-KEHATI (Jurnal Manajemen dan Kewirausahaan, 2015)
The objective of this research was described Indonesian capital market reaction to the publication of the SRI-KEHATI Index during 2009 until 2013 (nine periods). The results showed that the Indonesian capital market did not react to the SRI-KEHATI Index while measured using abnormal return, and these results were consistent for nine periods. However, different result occurred when it measured by trading volume activity, there was a market reaction in period 4, 6, dan 7, but there was no market reaction in period 1, 2, 3, 5, 8, and 9, it meant that the market reaction didn’t consistent.